Effects of different irrigation regimes and nitrogenous fertilizer on yield and growth parameters of maize - Shirazi, S.M.; Sholichin, M.; Jameel, Mohammed; Akib, Shatirah; Azizi, Mokhtar (2011)
A field experiment was carried out to find out the response on yield and yield contributing parameters of maize (cv. Bornali) to water stress and nitrogenous fertilizer. The experiment included two factors such as five irrigation regimes and four nitrogen levels. Texturally, the soil was silty loam. Yield and yield contributing characters were significantly affected due to the application of irrigation and nitrogen. The highest grain yield of 6.77 t/ha was obtained with IW/CPE ratio of 0.5 and 5.61 t/ha by the application of 70 kg N/ha. Interactions between IW/CPE ratio of 0.5 and 70 kg N/ha were the best combination for yield and yield contributing characters of maize.